INTEGRATION OF RELIGIOUS TRAVEL AND TOURISM IN JAVA - Pasya, Gurniwan Kamil; Gitasiswhara, Gitasiswhara (JURNAL PENDIDIKAN ILMU SOSIAL, 2013)
Pilgrimage has become one of religious activities developed by several countries in the world. The region that once was the center of religious development has attracted people to visit. Along with the development of Islam, Middle East countries become the main destination for the pilgrims. Due to high attention given to those countries, travel agencies design various outbond tour packages and offer them to Indonesian people while on the other hand, seem to neglect the fact that Indonesia, too has numerous Islamic heritage with great potential. Religious tourist destinations in Indonesia, particularly in Java is so diverse. TheÂ  development of history and culture in Indonesia is significantly influenced by the development of Islam in Java. Most tourism promotion is aimed to introduce the outside world as a major religious tourist destination to Indonesian market, despite the fact that Indonesia also has numerous sites of religious tourism. Religious tourism associated with the religion of Islam in Indonesia, particularly in Java such as in the form of the historical development of Islamic heritage, namely: The mosque founded by leaders of Islamic missionaries on the island of Java called Wali Sanga; Islamic imperial palace such as Kesultanan Cirebon, Kraton Surakarta and Yogyakarta Sultanate; The tomb of Wali Sanga in various places on the island of Java. Islamic religious tourism developments in recent time is highly associated with architectures, mosques, Islamic teaching and others. Islamic religious tourism development should not walk alone but integrated with other attractions because whenever there are religious tourist attractions, there are also other attractions such as nature tourism or cultural tourism. Methods: Desk research and literature study. Expected Results: The study is expected to generate a model of Islamic religious tourism destination management in Indonesia.Â Keyword: religious traveling (pilgrimage), the Islamic pilgrimage history.